1981
DOI: 10.1172/jci110079
|View full text |Cite
|
Sign up to set email alerts
|

Role of pH in production of hydrogen from carbohydrates by colonic bacterial flora. Studies in vivo and in vitro.

Abstract: A B S T R A C T Hydrogen produced by colonic bacteria and excreted in breath is a useful index ofcarbohydrate malabsorption. Since colonic contents are often acidic in individuals with carbohydrate malabsorption and in normal newborns, we determined the effect of colonic acidification on H2 production. Acidification of colonic contents by dietary means significantly reduced excess breath H2 excretion from 55.4+ 11.1 (SEM) to 12.2 ±3.1 ml/4 h (P < 0.05) after administration of 0.3 g/kg of the nonabsorbable suga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0
1

Year Published

1983
1983
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(68 citation statements)
references
References 24 publications
2
65
0
1
Order By: Relevance
“…Digestive tolerance of maltitol A Ruskone-Fourmestraux et al Prolonged ingestion of slowly absorbed sugars, such as lactose and lactulose, results in changes in the metabolic activity of the colonic flora, especially a fall in breath excretion of H 2 , which increases its ability to ferment the sugar (Florent et al, 1985;Flourié et al, 1993;Launiala, 1968;Perman et al, 1981). As a result, there is efficient fermentation of the chronically ingested unabsorbed sugar, and thus a reduction in its diarrhoeogenic effect (Rambaud & Flourié, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Digestive tolerance of maltitol A Ruskone-Fourmestraux et al Prolonged ingestion of slowly absorbed sugars, such as lactose and lactulose, results in changes in the metabolic activity of the colonic flora, especially a fall in breath excretion of H 2 , which increases its ability to ferment the sugar (Florent et al, 1985;Flourié et al, 1993;Launiala, 1968;Perman et al, 1981). As a result, there is efficient fermentation of the chronically ingested unabsorbed sugar, and thus a reduction in its diarrhoeogenic effect (Rambaud & Flourié, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The capacity to ferment unabsorbable sugars, such as lactose and lactulose, and to reduce their laxative effects can, however, be increased by regular ingestion of these sugars, which results in changes in the metabolic activity of the colonic flora, especially a reduced excretion of hydrogen in the breath (H 2 ) (Florent et al, 1985;Flourié et al, 1993;Launiala, 1968;Perman et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Information on the influence ofvarious factors on intracolonic bacterial H2 metabolism primarily has been obtained from in vitro studies of fecal homogenates (14)(15)(16). In all such studies H2 production was assumed to equal the volume of H2 recovered from the gas space of the incubation vessel.…”
Section: Discussionmentioning
confidence: 99%
“…However the accuracy of the H2 breath test in the study of chronic carbohydrate malabsorption is debated (1). Perman et al (7) showed that an 8-d oral administration of lactulose resulted in acidic stools and in a dramatic fall of H2 breath excretion after an oral load of this sugar or of lactose in Received for publication I August 1984. lactase-deficient patients. From stool homogenate incubations with various sugars, these authors concluded that the fall of H2 production was due to an inhibition of bacterial carbohydrate metabolism by the low colonic pH (7).…”
Section: Introductionmentioning
confidence: 99%
“…In the first part of our study, Perman et al (7) protocol design was applied to four normal subjects. Hydrogen breath excretion was found reduced after the 84 lactulose administration; however, fecal pH did not decrease and carbohydrates were not excreted in stools, whereas $-galactosidase fecal output increased significantly.…”
Section: Introductionmentioning
confidence: 99%